PENTINGNYA KEADILAN RESTORATIVE JUSTICE DALAM TINDAK PIDANA PENCURIAN OLEH ANAK BERDASARKAN HUKUM POSITIF DI INDONESIA - Alivia, Annisa; Moh. Andika Surya Lebang (SCIENTIA JOURNAL, 2024)
Restorative justice offers an innovative approach to dealing with children in conflict with the law. Children and teenagers must be protected from various dangerous influences that can cause juvenile delinquency and lead to criminal acts. In Indonesia, crimes are punished based on court decisions. However, if it is done to children, it can have a negative impact on their future development. The Restorative Justice approach in the context of theft allows minor perpetrators to understand the consequences of their behavior for the victim. Apart from that, there is the concept of diversion, namely diversion which takes the form of counseling, education or social work to achieve restorative implementation. Restorative Justice allows children as perpetrators, victims and families to sit together to mediate or deliberate to solve and resolve the problem of the child's act of theft. To create peace results from an agreement between the two parties or by means of affirmation against the perpetrator such as returning goods that have been stolen or providing compensation. The research method used is normative legal research. In this research, the main source used is based on Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, and uses other literature, for example journals and books related to this research. Restorative-related research can explore the importance of restorative justice in the context of protecting children involved in the legal system. Through a literature review, this research shows that restorative justice not only provides a more humane alternative in handling crimes against minors but also makes a positive contribution to the process of rehabilitation and reintegration of children into society. Apart from that, it is certainly better than settling through court.